Factors That Influence The Appointment Of Service Providers In Gauteng Department Of Roads And Transport - Mokwena, Karabo Dickson; Naidoo, Vinessa (Archives of Business Research, 2020)
Many South African roads experience inadequate construction and maintenance. The road construction scantiness is evidenced by the Moloto Road, Gauteng, Mpumalanga and Limpopo. This was dubbed the “notorious road” for the high number of fatal accidents. An assessment of factors influencing the appointment of service providers might be a profound strategy to ensure efficiency and effectiveness in the construction and maintenance of South African roads. The factors under study included financial stability and resources indicators, quality, environmental and safety indicators, management ability, technical capacity and past experience and performance in appointing service providers. This study sought to determine the importance and influence of the factors affecting the successful appointment of service providers within the Gauteng Department of Roads and Transport. A quantitative descriptive approach, with the use of a structured questionnaire was utilised to collect data from a sample of 155 employees of Gauteng Department of Roads and Transport within the City of Tshwane. Descriptive and multivariate analyses including factor correlations and regression analyses were conducted. Some important factors identified when choosing service providers were financial stability and resources indicators, quality, environmental and safety indicators, management ability and experience and performance. Technical capacity was found to be less important. A significant positive relationship was found between factors for choosing service providers and the selection of competent service providers. The results of this study greatly corresponded with the literature review. The same factors were identified as influencing the successful appointment of service providers in this department.